Pengaruh Kualitas Produk Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada Rahastra Credit Union Bandung - Listianti, Yulia (SEIKO : Journal of Management & Business, 2024)
This research was conducted at Rahastra Credit Union Bandung, aimed to know the correlation of product quality, service quality, and customer satisfaction, and also to analyze the impact of product quality and service quality to customer satisfaction at Rahastra Credit Union Bandung. Respondents of this research are 84 people, selected using incidental sampling technique. The method use is descriptive and associative, which tests the influence of dependent and independent variables using path analysis, and also done to determine the accuracy of measurement using validity and reliability test. Result of the validity and reliability test of variables X and Y express all valid and reliable. The result showed that product quality is in the category of good, service quality is in the category of good, and customer satisfaction is in the category of good at Rahastra Credit Union Bandung. The result of partial test showed that product quality and service quality partially impact customer satisfaction, with the t-count value for variables of X1 and X2 is greater than the t-tabel value (3,927 and 4,875 > 1,990). The result of simultaneous test showed that product quality and service quality have an impact significantly to customer satisfaction, with the value of Adjusted R-Square = 0,508 and the path equation is Y = 0,364 X1 + 0,452 X2 + υ. This result showed that the hypothesis is proved: there are the impact of product quality and service quality to customer satisfaction at Rahastra Credit Union Bandung, either partially or simultaneously. Keywords: Product Quality; Service Quality; Customer Satisfaction.